Stories of your life and others - Chiang, Ted (Vintage Books, a division of Penguin Random House LLC, 2016)
"Stories of Your Life and Others is a collection of masterpieces and recently it has taken Hollywood by storm. The lead story in the collection will soon to be a major motion picture starring Amy Adams, while another story has been optioned by Fox and is in development. Offering readers the dual delights of the very strange and the heartbreakingly familiar, Stories of Your Life and Others presents characters who must confront sudden change. In the amazing and much-lauded "Story of Your Life," a grieving mother copes with divorce and the death of her daughter by drawing on her new knowledge of an alien language and its nonlinear structure. In "Liking What You See: A Documentary," a clever pastiche of news reports and interviews chronicle a college's initiative to turn off the human ability to recognize beauty. In "Understand," a young man has an amazing reaction to an experimental drug used to heal brain damage. In each story, with sharp intelligence and humor, Chiang examines what it means to be alive in a world marked by uncertainty, but also by wonder"--